(untitled) (Bangladesh Medical Journal Khulna, 2016)
A Case Control study was carried out to identify the risk factors of Coronary Heart Disease (CHD) at Mymensingh Medical College Hospital. As many as 96 patients were selected purposively as cases who were admitted with CHD at Coronary Care Unit, whereas an equal number of age, sex and religion matched controls were selected from patients admitted into Medicine Units during the study period. Data were collected by using pretested interview schedule after obtaining informed verbal consent. The mean age of the cases and controls, were 58.88 years with a Standard Deviation of 10.52 years. A highest number of cases and controls (87-90.62%) were males, while the rest 9 (9.38%) were females. Among cases 27 (28.13%) were illiterate, while of controls, 36 (37.50%) were illiterate. The association of smoking with the development of Coronary Heart Disease was statistically significant (P<O.05) with an odds ratio of 2.07. Family history of CHD had a very high statistical significance (p<0.001) with odds ratio 3.53. High statistical significance (p<0.01) was also observed between Diabetes Mellitus and Coronary Heart Disease with an odds ratio of 3.34. Coronary Heart Disease can be prevented through primordial prevention by hindering the development of baneful behaviours like habit of smoking, chewing betel leaf, use of tobacco and jarda, having fatty diet like meat. Bang Med J (Khulna) 2015; 48 : 28-31